MAKNA ISLAM KAFFAH DALAM KITAB TAFSIR AL-RAZI - Permana, Fadhila Sidiq (UIN Sumatera Utara Medan, 2025)
In response to the fundamentalist ideologies that often display the slogan of Islam kaffah, it is very important to revisit the concept of Islam kaffah in the interpretation of the Qur'an. This article aims to provide a scientific response through an authoritative traditional interpretation study, namely the book Mafatih al-Ghaib by Fakhruddin al-Razi. The method used in this research is literature study, where the theme of 'Islam kaffah' is examined through the perspective of al-Razi's interpretation. The results of this study conclude that Islam kaffah is not merely about carrying out all aspects of religious teachings, but also about efforts to continuously improve the quality of faith and religious practice. The subsequent conclusion explains that the interpretation of Islam kaffah is not singular and is not intended solely for the welfare of Muslims, but also for the welfare of all humanity regardless of their religious background.